A monospectral approach for fMRI analysis using Kohonen self-organised networks and objective dialectical classifiers. (13th July 2009) - Dos Santos, Wellington P.; De Assis, Francisco M.; De Souza, Ricardo E.; Albuquerque, Ana Cristina T.; , Maria Lucia B. Simas
One of the major challenges at the field of cognitive sciences is mapping the regions of the brain responsible for the motor and behavioural functions. The acquisition of functional magnetic resonance images is an important non-invasive technique to study the neural activity in the human brain. The dialectical conception of reality is a kind of philosophical investigative method for analysing processes present in nature and in human societies. The dialectical method is a tool for studying systems by considering the dynamics of their contradictions, as dynamic processes with intertwined phases of evolution and revolutionary crisis. It has inspired us to conceive a dialectical classifier able to solve classification problems. This work presents a new approach for the detection of activated brain regions: the composition and analysis of synthetic multi and monospectral images using statistical methods and proposing a non-parametrical method based on Kohonen self-organised networks and in objective dialectical classifiers.